IMPULSIVE BUYING ON SOCIAL MEDIA PLATFORMS: A BIBLIOMETRIC REVIEW - Bashar, Abu; Singh, Dr. Shalini (The journal of contemporary issues in business and government, 2022)
Online impulse buying behaviour is one of the most important areas of research in social commerce setup. Web 2.0 has revolutionised the concept of online commerce through social networking sites and so the impulsive buying patterns. Given the importance of the area, our paper is dedicated to find out the recent development in this area of research. Bibliometric analysis coupled with network analysis is used to review the literature from 2003-2021. A total of 120 articles have been reviewed and analysed using Biblioshiny of R Studio package and VOSviewer software.Best documents, most used references, popular keywords most influential author, most contributing affiliations, countries, and word growth trend have been presented through bibliometric analysis. Also, with the help of network analysis, citations, co-citations, co-authorship, and bibliographic coupling is conducted to identify the research streams/clusters and collaborations among authors/organisation. The research limitations and future research direction have been enumerated and presented for further expansion.